Perbandingan Rekrutmen Karyawan Menggunakan Metode Simple Additive Weighting (SAW), Weighted Product (WP), Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Gagan Hariyanto; Alfiansyah Awaludin; Aep Rusmana; Kukuh Ilham Perdana; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Technology in the current era is experiencing very rapid development, as time goes by the need in the world of work for information and data for recruiting employees is getting easier. With the existence of a decision support system, it is an arrangement of computer-based information systems that function as decision support in an organization or company. Making the right decision will make an organization. that achieves its goals properly. The decision support system method is useful for taking alternatives based on certain criteria and weights, including the Simple Additive Weighting, Weighted Product, Technique For Order Preference by Similarity to Ideal Solution methods. A comparison of the decision support system methods will give the highest value of the research results for employee recruitment. Based on a comparison using the three methods, V1 has a higher yield value and ranking than the others.